Investigations on Some Physicochemical Parameters of Demirköprü Dam Lake (Manisa, Turkey) - Saniye Türk Çulha; Mirati Erdoğuş (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out at 3 different stations in Demirköprü Dam Lake, Köprübaşı, situated in Manisa, between June 2015 – May 2016. Samples collected from the surface and the bottom of the lake were analyzed seasonally in terms of depth (m), temprature (°C), dissolved oxygen (DO), pH, salinity (‰), total dissolved solids (TDS), electrical conductivity (EC), secchi disk depth (SD), suspended solid matter (SSM), particulate organic matter (POM), particulate inorganic matter (PIM), ammonium nitrogen (NH4+-N), nitrite nitrogen (NO2--N), nitrate nitrogen (NO3--N), phosphate phosphorus (PO4-3-P), silica (SiO2) and Chlorophyll-a parametres. As a result of this study, according to Inland Water Quality Standards defined in ʽʽSurface Water Quality Management Regulations’’ Demirköprü Dam Lake can be considered; Class-I quality according to measured temperature (15±1.3°C), NO2--N (0.010±0.003 mg/l) and NO3--N (0.04±0.01 mg/l) values; Class-II quality according to measured DO (6.86±0.90 mg/l), EC (591±6.4 µS/cm), SSM (5.90±6.40 mg/l), NH4+-N (0.30±0.09 mg/l) and PO4-3-P (0.08±0.01 mg/l) values; Class-III quality according to measured pH (8.72±0.09) values. Also, according to Turkish Boundary Values of Trophic Classification System of Lakes, Ponds and Reservoirs; the trophic level of the lake is considered eutrophic in regard to PO4-3- and SD values and hypereutrophic in regard to Chlorophyll-a values.